Contaminant removal from rectangular shaped pipeline joints using constrained interpolated profile method - Zain Ashraf Abd. Malek, 1987; Nor Azwadi Che Sidik, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012